RELATIONSHIP BETWEEN FACTORS IN REGULATION OF CHILDREN’S BEHAVIOR AND THEIR DENTAL STATUS - Koval, O.I. (World of Medicine and Biology, 2020)
A child’s health is based on his upbringing. The child’s behavior at the dentist’s visit, the child’s attitude to oral hygiene: all this reflects the behavior of parents in family relationships and their attitude to dental health in general. The pediatric dentist must take into account the peculiarities of the style of parental upbringing to achieve the aim of forming a positive attitude to the child’s dental treatment in the future. The article presents the results of determining the dental status of children depending on the main forms of parenting style. According to the results of dental treatment, the choice of conditions for dental rehabilitation is substantiated and the influence of parenting style on the formation of dental health in children is studied.